Annual bluegrass weevil (Listronotus maculicollis) and paclobutrazol control annual bluegrass (Poa annua) in creeping bentgrass fairways. (26th February 2022) - Diehl, Katherine H.; Elmore, Matthew T.; Koppenhöfer, Albrecht M.; Murphy, James A.; Kostromytska, Olga S.
Abstract: The annual bluegrass weevil (ABW) is a pest of fine turfgrass, but recent research has found that withholding insecticides for ABW control can reduce annual bluegrass cover. The objective of this research was to evaluate threshold-based insecticide and paclobutrazol programs for annual bluegrass control. The effect of three insecticide programs (preventive, threshold, and no insecticide) and four rates of paclobutrazol (0, 70, 105, or 210 g ha −1 applied monthly) were evaluated. Replicate experiments were conducted from April to November in both 2018 and 2019 on a mixed creeping bentgrass and annual bluegrass fairway in North Brunswick, NJ. By the conclusion of both experiments, all paclobutrazol programs exhibited reduced annual bluegrass cover compared with the nontreated plots. In threshold and no-insecticide programs, reduction in annual bluegrass cover was enhanced by paclobutrazol applied at 105 g ha −1 in both years, and at 70 g ha −1 in the 2019 experiment. Paclobutrazol at 210 g ha −1 resulted in annual bluegrass cover of <20% regardless of insecticide program. In 2019, threshold-based ABW control without paclobutrazol provided similar annual bluegrass control as monthly applications of paclobutrazol at 70 and 105 g ha −1 with the preventive insecticide program. A reduction in turfgrass quality from threshold-based insecticide programs persisted for a shorter duration than the no-insecticide program, regardless of paclobutrazol treatment. Threshold-based ABW insecticide programs that allow ABW feeding damage to occur can result in reduced annual bluegrass cover. These reductions were further enhanced by paclobutrazol applications. The combination of threshold-level insecticide with moderate rates of paclobutrazol (70 to 105 g ha −1 ) provided reductions in annual bluegrass cover that were similar to the highest rate of paclobutrazol (210 g ha −1 ) without ABW damage. Turfgrass managers who integrate the threshold-level insecticide approach and monthly paclobutrazol applications may achieve greater annual bluegrass control than either strategy alone if temporary reductions in turf quality can be tolerated.